Photosynthesic performance and DNA mutation of tropical, temperate and polar Chlorella species (chlorophyta) subjected to short-term UVR stress / Jeannette Lai Wai Shan - Jeannette Lai , Wai Shan (2018)
The increase in ground ultraviolet radiation (UVR) levels due to ozone depletion is one of the seriously debated issues among environmental scientists. UVR can cause detrimental biological impacts to photosynthetic organisms. The current research focused on the effects of short-term UVR stress on the (1) photosynthetic responses and the (2) DNA mutation in Chlorella species from tropical, temperate, Antarctic and Arctic regions. In this study, photosynthetic performance of Chlorella post UVR treatment was determined using Pulse-Amplitude-Modulation (PAM) fluorometry, which is based on the determination of chlorophyll fluorescence. During photosynthesis, a small amount of the solar energy is absorbed and transformed into chemical energy while the rest are dissipated as heat and released as fluorescence. An increase in one of the process will result in a decrease in the other two as these three rate constants are in equilibrium. Thus, changes in photosynthesis efficiency and heat dissipation can be detected by measuring the yield of chlorophyll fluorescence, and this can also be used as an early indicator of stress. The photosynthetic parameters determined in this study by using PAM flurometry are: maximum quantum yield (Fv/Fm), photosynthetic efficiency (α), maximum electron transport rate (rETRm) and photoadaptive index (Ek). On the other hand, DNA mutation can be assessed via the Random Amplified Polymorphic DNA (RAPD) analysis which detects genetic variation ranging from changes in a single nucleotide to complex chromosomal rearrangements, by comparing the amplification products generated from the control (untreated sample) and treated samples. Three light treatments: (i) control (Photosynthetic active radiation, PAR), (ii) PAR+UVA (UVA stress) and (iii) PAR+UVA+UVB (UVB stress) were conducted over a continuous, five-hour duration in this study. Chlorella species subjected to PAR (control) treatment did not show significant photosynthetic dysfunction, as reflected by the insignificant change in the values of Fv/Fm, α, rETRm and Ek. However, UVB radiation has an apparent negative impact on the mentioned v photosynthetic parameters in all strains whereas only tropical isolate showed significant photosynthetic effect under UVA treatment. In addition, no significant changes were observed for the photosynthetic pigment contents (chlorophyll a and carotenoids) and chl a: carotenoids ratio in all treatments. Although no significant photosynthetic dysfunction was detected in all Chlorella strains subjected to UVA treatment, RAPD analysis revealed DNA mutation caused by both UVA and UVB treatments in all strains. In addition, the photosynthetic performance of Chlorella spp. appeared origin-dependent, which could be important in ensuring optimal survivability in different habitats.